THE EFFECT OF SCAFFOLDING GUIDANCE PROMPTING TECHNIQUE IN GUIDED-INQUIRY LEARNING ON STUDENTS' SCIENCE PROCESS SKILLS IN BUFFER SOLUTION CONCEPTS - Marini, Cintia; Hasibuan, Muhammad Haris Effendi; Sanova, Aulia (Chimica Didactica Acta, 2025)
The purpose of this study is to determine the influence of applying scaffolding Guidance prompting strategy in guided-inquiry learning model on students' science process skills (SPS) in buffer solution concepts of senior high school students. This study also addressed how the prompting technique caused the effect on the SPS. Hence, the study used A mixed method research methodology with a sequential explanatory approach, integrating the quantitative and the qualitative data to answer the aims. A SPS-related observational sheet was used to collect data about two classes students skills in doing practicum. A SPS-oriented test was used to collect data about the students understanding of SPS. In addition, a field notes observational sheet was used to collect data about factors causing the development of students SPS. The results showed the experiment groups SPS score was higher than the control groups SPS score (77.57 and 82.50) in observing skill, and this was the same with the experiment groups SPS who had higher classifying skill compared to the control groups SPS (64.70 and 70.33). The t-test results verified that there was a difference between the two groups' test indicated by the p-value (sig) 0.05. This means the use of prompting technique was effective in nurturing the experiment groups SPS. Based on field observation, it was clear that the use of the prompting technique was very helpful for the experiment group to conduct the experiment.